Outcome-Based Curriculum (OBC) in Arabic Language Education: An Epistemological Analysis in Islamic Education Perspective Based on Rusdi Ahmad Thuaimah’s Thought - Buhori Buhori; Sutaman Sutaman; Bisri Mustofa (SYAMIL: Journal of Islamic Education, 2025)
This study examines the development of an Outcome-Based Curriculum (OBC) in the Arabic Language Education Study Program (PBA) at IAIN Pontianak through an epistemological analysis grounded in Rusdi Ahmad Thuaimah’s thought. The research was motivated by the need to reconcile competency-based higher education reforms with the philosophical and pedagogical foundations of Arabic language education. Using a qualitative descriptive case-study design, data were collected from curriculum documents, interviews, observations, and institutional records, and analyzed through interactive qualitative analysis to identify structural, epistemological, and pedagogical patterns. The findings indicate that the PBA curriculum has evolved into an integrated OBC framework encompassing curriculum foundations, graduate profiles, CPL, and a tiered course structure aligned with national standards and Islamic sociocultural values. Epistemologically, it reflects Thuaimah’s view of Arabic as communicative, cultural, and cognitive practice, operationalized into measurable competencies, multidimensional graduate roles, and constructive alignment between learning design and authentic assessment””demonstrating compatibility between OBE principles and Arabic curriculum epistemology. The study concludes that meaningful curriculum reform in Arabic language education depends on the systemic integration of epistemology, curriculum design, and assessment practice rather than structural redesign alone. Practically, the integrative model requires strengthening communicative-experiential learning, performance-based assessment, lecturer pedagogical capacity, and institutional quality assurance. Future research should empirically test the model across institutions, track graduate outcomes longitudinally, and explore digital integration within OBE-oriented Arabic curricula to support adaptive curriculum development in Islamic higher education.